(untitled) (Journal of Humanitarian and Applied Sciences, 2026)
Corrosion of metals is a serious challenge for many industries. Green corrosion inhibitors offer an eco-friendly and biodegradable alternative to traditional chemicals. This study aimed to evaluate the effectiveness of Citrus limon leaf extract as a green inhibitor for mild steel corrosion in a neutral 3.5% NaCl saline solution. The plant was extracted using 80% ethanol, and inhibition efficiency was assessed by the weight loss method at different extract concentrations, temperatures (30–60 °C) and immersion times (4–72 h) The results showed that the extract had a maximum inhibition efficiency of 88.65%. The inhibition efficiency increased with higher extract concentration and longer immersion time but decreased with higher temperature, suggesting the formation of a protective layer on the metal surface. Based on these findings, Citrus limon extract has shown promising potential as a green corrosion inhibitor. Further research is recommended to elucidate the inhibition mechanisms and application conditions for practical use.